Sosialisasi Penulisan Artikel Ilmiah dan Strategi Publikasi - Fitri Maghfirah; Shira Thani; Fitria Mardhatillah; Muksalmina; Eko Gani PG (Wisanggeni: Jurnal Pengabdian Masyarakat, 2022)
Scientific writing, which includes journal articles, has a role that has a positive impact on career development in a profession as well as the development of knowledge. Scientific work is also one of the important things for students, teachers and lecturers, both for obtaining graduation from one level of education and for the benefit of a work portfolio. Even so, there are still many who do not understand the preparation of scientific articles and the publication process. Therefore, the results obtained through this activity are increasing the knowledge of workshop participants consisting of students, general academics, and lecturers within the Malikussaleh University campus environment regarding scientific article writing and the publication process. This dedication is also very important to carry out, considering that there are still many parties who do not understand scientific articles in particular. What's more, with this workshop, of course, it is very helpful to motivate many parties to try to write and seek many ways of solving problems related to issues in society. As is commonly known, that the purpose of knowledge is to provide solutions to every problem that exists in society, and this can be obtained through research which can then be reported through scientific writing.